Air pollution and public health in developing countries: Is Sri Lanka different? - S Nandasena; AR Wickremasinghe; N Sathiakumar (College of Community Physicians of Sri Lanka, 2012)
Indoor and outdoor air pollution is a major public health challenge in developing countries and much concern has been raised among policy makers, public health experts, clinicians, and the general public in recent years. A spectrum of health outcomes has been shown to be associated with exposure to air pollution in epidemiological studies and by laboratory investigations. It is estimated that indoor air pollution resulting from exposure to solid fuel accounts for over 1.5 million premature deaths and 38.5 million Disability-Adjusted Life Years. Globally, it is estimated that outdoor air pollution accounts for over 800,000 premature deaths and 6.4 million years of life lost; of these numbers, 65% is from Asia alone. There is emerging evidence that the actual burden is much larger than the estimated values. The World Health Organization has estimated the number of deaths attributable to indoor air pollution and outdoor air pollution in Sri Lanka to be 4200 and 1000 deaths, respectively. Although country information is limited, a few epidemiological studies gives us the opportunity to understand and compare the Sri Lankan situation vis a vis other countries. This includes the 16 epidemiological studies identified by a scientific review in 2010 and several other published studies and preliminary data from ongoing studies. DOI: http://dx.doi.org/10.4038/jccpsl.v17i1.4932 Journal of the College of Community Physicians of Sri Lanka Vol.17(2) June 2012 21-42